Análise da acessibilidade física e informacional de museu para a população usuária em contexto de evacuação de emergência - Silva, Jeovana Cecília Fernandes da (2024)
Museums are institutions that were created to acquire, conserve, investigate, disseminate and exhibit the material testimonies of humanity and its surroundings, to promote education, citizenship, culture, enjoyment and quality of life in society. Even though they hold works of cultural and material value, have employees and receive a diverse visitor population, many museums lack, or partially have, accessibility and disaster prevention and response systems, in particular, an emergency evacuation system. This research project aims to analyze the accessibility and emergency evacuation conditions of museums in the city of Natal, Rio Grande do Norte, and the preparation of the user population (employees and visitors) for safe evacuation from the museum in an emergency context. The population studied in this research comprised employees and visitors to the museums in question. Initially, a bibliographical search was carried out on the topic of this research in the Periódicos Capes virtual library and documentary research on standards and legislation on accessibility, emergency and evacuation systems. Then, using the Global Analysis Guide for Museums, a survey and general characterization of existing museums in the city of Natal were carried out, in which a standard checklist was applied to evaluate the compliance of accessibility and systems or devices emergency and evacuation of each museum for the user population. Then, based on the Ergonomic Work Analysis (EWA), a case study was carried out in one of the museums in the city of Natal/RN, which was chosen for convenience. In the case study, the Case Study Museum's Global Analysis Guide was applied, to understand its structure, organization and global functioning, the Visitation Observation Plan, to identify accessibility problems, and the Conversation Guide with employees, museum managers and visitors to analyze their perception regarding accessibility, risks, emergency systems and evacuation. Also, a simulated exercise was carried out, with an emergency scenario inducing the evacuation of the museum's user population, to analyze their behavior in the face of the simulated emergency situation. To assess the perception of risk and the museum's accessibility, emergency and evacuation systems by the user population, a questionnaire was administered immediately before and after the simulated exercise. Also, immediately after the simulated exercise, the Conversation Script was applied to the user population that participated in the simulation to comment on the emergency scenario applied and the museum's accessibility, emergency and evacuation systems and their relationships with the behaviors assumed by them. in front of the simulated scenario. It was observed that museums that had their accessibility and emergency compliance assessed needed improvements in both the physical and informational accessibility system and the emergency system. It was also observed that the simulated exercise carried out in the case study museum contributed to sharpening the participants' risk perception and improving the museum's accessibility and emergency system. This research contributes to the theoretical and methodological knowledge of Ergonomics and Accident or Disaster Risk Management, considering the application in museums, and, from a practical point of view, to the efficiency of emergency evacuation of the case study museum and to the improvement of public policies, management and architectural and emergency projects for museums, with regard to the safety of the user population in emergency situations.